Burnout and depression in nurses: A systematic review and meta-analysis. (December 2021) - Chen, Chiahui; Meier, Scott T.
Abstract: Background: Nurses work in stressful and demanding settings and often suffer from depression and burnout. Despite overlapping symptoms, research has been inconclusive regarding the discriminant validity of measures of burnout with regard to measures of depression. Such inconclusive discriminant validity might cause clinicians to fail to recognize and manage depression separately from burnout. Objectives: This meta-analysis aimed to clarify the distinctiveness of burnout as a separate construct by examining the size of the relationship between burnout and depression among nurses as well as potential moderators. Method: A stepwise method was used by searching 4 databases (PubMed, CINAHL, PsycINFO, and EMBASE) to retrieve published papers in English examining the relationship between burnout and depression among nurses and reporting the effect sizes of their findings. Results: We identified a total of 37 eligible studies. The pooled estimate showed a positive association between burnout and depression among nurses ( r  = 0.403, 95% CI [0.327, 0.474], p  < 0.0001) and a slightly higher correlation coefficient for the Emotional Exhaustion subscale of the Maslach Burnout Inventory (MBI) measure (0.494, 95% CI [0.41, 0.57]). Conclusions and Implications: This review confirms a large burnout - depression correlation in nursing samples, adding to existing literature encompassing a variety of occupations. Future studies should focus on path analysis to assess the causal relationship as well as investigate potential moderators.